(untitled) (Damascus University Journal of arts and humanities sciences, 2024)
The research aims to identify the level of both work pressure and job performance among workers in the Education Directorate of Rural Damascus, and the impact of work pressure on job performance, and to identify the significance of the differences in the work pressure scale and the job performance scale according to the research variables (sex, occupational category), and the researcher adopted the descriptive approach. Analytical questionnaire, and the questionnaire as a tool for research, consisting of two parts (questionnaire work pressure, and questionnaire job performance), where the research sample amounted to (299) factors from the Directorate of Education in the countryside of Damascus. . The results showed that the level of work pressure in the Education Directorate of Rural Damascus came to a high degree, while the job performance level of the workers was at an average level. There are statistically significant differences between the averages of the respondents’ responses to the work performance scale and the job performance scale according to the job category variable and in favor of the first category workers.